TERAPI KORTIKOSTEROID PADA PEMPHIGOID MEMBRAN MUKOSA MULUT DAN EFEK SAMPINGNYA (LAPORAN KASUS) - Andrian Nova Fitri; Siti Aliyah Pradono (Faculty of Dentistry, Universitas Indonesia, 2015)
Mucous membrane pemphigoid (MMP), also known as cicatrical pemphigoid, is a chronic, autoimmune, subepithelial blistering disease primarily affecting people over 50 years old. MMP may affect any mucosal surface, which is particularly oral mucosa, conjuctiva, esophagus, or larynx is involved. MMP rarely occurs in children and adolescents, but several cases of MMP affecting 2 to 18 years old patients old male patient who had been diagnosed with oral mucous membrane pemphigoid by anamnesis, clinical feature, histopathology. The patient was treated with systemic corticosteroid, topical corticosteroid, oral rinse and multivitamins. Until recently corticosteroid remains as the most effective and the drug of choice to treat pemphigoid lesions. Clinicians need to pay attention in using this drug because of its potential side effect.